2021
DOI: 10.11591/eei.v10i1.2474
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity prediction using fitness data: Challenges and issues

Abstract: In the new healthcare transformations, individuals are encourage to maintain healthy life based on their food diet and physical activity routine to avoid risk of serious disease. One of the recent healthcare technologies to support self health monitoring is wearable device that allow individual play active role on their own healthcare. However, there is still questions in terms of the accuracy of wearable data for recommending physical activity due to enormous fitness data generated by wearable devices. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The gradient boosting framework is used by the decision tree-based ML method known as XGBoost [56], [57]. XGBoost was created by Tianqi Chen and was first kept up by the distributed (deep) machine learning community (DMLC).…”
Section: Xgboost With Vital Feature Combination Algorithmmentioning
confidence: 99%
“…The gradient boosting framework is used by the decision tree-based ML method known as XGBoost [56], [57]. XGBoost was created by Tianqi Chen and was first kept up by the distributed (deep) machine learning community (DMLC).…”
Section: Xgboost With Vital Feature Combination Algorithmmentioning
confidence: 99%
“…He categorized and structured the published research evidence in the field of machine learning techniques for predicting physical activity using fitness data based on personal background and fitness data to predict appropriate physical activity. This research provided new insights into software development in healthcare technology to support the personalization of individuals in managing their own health (1). Wang H conducted inquiries, modifications, additions, deletions, etc.…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [ 17 ] applied the Fogg behavior model and the transtheoretical behavior model to predict physical activity. In [ 18 ], the authors examined the association between physical activity and the expiratory to inspiratory (E/I) ratio of mean lung density (MLD) and showed that the E/I ratio of MLD could be a useful imaging biomarker for the early detection of physical inactivity in COPD patients.…”
Section: Introductionmentioning
confidence: 99%